FORMULATION AND IMMUNOMODULATORY BIOACTIVITY TEST OF NANOPARTICLE SYRUP OF ETHANOL EXTRACT OF SUNGKAI LEAVES (Peronema canescens Jack) - Haflin; Agusriani; Kartika Mustofa; Ruri Putri Mariska; Rizky Yulion; Pitriani; Shafira Al Fadhilah; Barmi Hartesi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Sungkai plants are beneficial immunomodulators because of the presence of flavanoid compounds that increase oxygen radicals and antibody production. Pharmaceutical preparations function as immunomodulators, typically in the form of syrups, tablets, capsules, suspensions, and emulsions. Until now, there has been no nanoparticle syrup on the market, even though nanoparticle preparations have the advantage of modifying particle size, controlling the release of active ingredients to reach the active side, protecting drugs from degradation, reducing toxicity, and minimizing side effects. The purpose of this study was to determine whether the syrup of nanoparticles in the ethanol extract of Sungkai leaves acts as an immunomodulator and the stability of the preparation during storage. The methods used were experimental in the laboratory with extraction using the maceration method. The extract obtained was formulated into a nanoparticle solution using the ionic gelation method, then formulated into FO syrup (Base syrup) and F1 syrup (Nanoparticles of ethanol extract of sungkai leaves) and then carried out transmittance tests, particle size analyzer tests, immunomodulatory tests and stability tests. The yield of the extract was 17.5%. The raw material examination of all the materials was in accordance with the literature. The particle size of the nanoparticle solution was 40 nm, that of F0 syrup was 670 nm, and that of F1 syrup was 964 nm. All syrup preparations fell into the nanoparticle size category of 10–1,000 nm. The leukocyte count of the negative control treatment (syrup base) was 5,011 cells/mm³, ...